THE ROLE OF INTELLECTUAL AGILITY, ENTREPRENEURIAL DEVELOPMENT, AND ONLINE SALES PROCESS IN IMPROVING THE PERFORMANCE OF EMBROIDERY ENTREPRENEURS - Anis, Nusron (STIE PGRI Dewantara Jombang, 2023)
This study analyses the effect of intellectual agility, entrepreneurial development, and online sales process on performance. This study uses a quantitative approach. The population in this study are all embroidery entrepreneurs in Pasuruan who have been selling online for at least the last two years, the number of which is unknown with certainty. The sample used in this study amounted to 180 respondents obtained randomly. The results show that intellectual agility, entrepreneurial development, and the online sales process significantly affect company performance. Intellectual agility has a significant effect on the online sales process. Entrepreneurial development does not affect the online sales process. From the research results, it is also known that the online sales process can mediate the influence of intellectual agility on company performance but cannot mediate the effect of entrepreneurial development on company performance.